Design and Evaluation of Sequential Near-Bottom Mobile Organism Sampling Equipment Intended for Deep-Sea Mining Plume-Affected Zones - Kaichuang Wang; Haiyang You; Xinghui Tan; Jiale Wu; Bo Han; Junyi Yang; Congchi Huang; Jiawang Chen; Jin Guo (Journal of Marine Science and Engineering, 2026)
Deep-sea mining generates plumes containing heavy metals harmful to marine ecosystems. Assessing their impact on benthic organisms is essential. Traditional monitoring methods commonly employ acoustic, optical, and electrical approaches to investigate collective behaviors of organisms, while direct acquisition and in situ preservation of biological specimens during deployment remain challenging. To address this limitation, a novel sequential near-bottom mobile organisms sampling equipment equipped with multiple chambers was developed. Sequential sampling of near-bottom mobile organisms was conducted to obtain samples at different time points for individual-level biological assessment. This study investigates the alcohol diffusion dynamics at various injection volumes. The results show that during injection, alcohol is concentrated in the upper section of the chamber. When 5.0 L of alcohol is introduced, the alcohol mass fraction within the sampling container rapidly reaches and stabilizes at 87%. The sampling equipment’s performance was evaluated through dock experiments and deep-sea trials at a depth of 1571 m in the South China Sea. Field tests successfully captured five jellyfish, with alcohol mass fractions of 85%, 87%, and 87% achieved in the respective chambers. These results demonstrate the feasibility of the equipment for sequential biological sampling and in situ preservation in deep-sea environments.